Activated polymeric materials for phosphorus removal in aqueous medium: Study of kinetics and adsorption isotherm - Kari Ferro, Aydeé (2026)
Excess dissolved phosphorus can cause eutrophication of water bodies. Various porous materials have been proposed to reduce P levels to acceptable levels. The study aimed to evaluate the phosphorus adsorption potential in aqueous media at pH 5, 6, and 8 through citric acid esterified cellulose nanocrystals (NCC), NaCl activated clay (AA), and atomized Nostoc sphaericum hydrocolloid (NS-AH). ζ potential, particle size, zero charge point, total inorganic carbon, TGA, DSC, XRD, and FTIR analysis of the adsorbent materials were determined. The adsorption capacity of P was 16.17, 13.45, and 9.25 mg/g, and removal up to 89.44, 70.35, and 51.66 % by NCC, AA, and NS-AH respectively from 20 ppm P solution. The PFO, PSO, and Intraparticle Diffusion kinetic models were studied, indicating high adsorption rate for AA and NCC during the first 20 min. The study of Langmuir, Freundlich, Redlich-Peterson, Temkin, and Dubinin Radushkevich isotherms showed that the adsorbents present heterogeneous surface, high porosity, and affinity for P at pH 8 in the order NCC > AA > NS-AH and that adsorption is spontaneous and favorable, governing chemisorption processes. The proposed materials, mainly NCC and AA, present high potential for P removal in aqueous media.